QUALITY OF LIFE, FORCED EXPIRATORY VOLUME IN ONE SECOND AND BODY MASS INDEX IN PATIENTS WITH COPD, DURING THERAPY FOR CONTROLLING THE DISEASE - Stojkovic J.; Stevcevska G. (Macedonian Academy of Sciences and Arts, 2009)
Abstract: Patients with chronic obstructive pulmonary disease (COPD) are characterized by an impaired lung function and limited exercise tolerance. Medication and rehabilitation programmes are generally directed towards relief of symptoms and improvement of lung function and exercise tolerance. 130 patients were included in the examination with diagnosed chronic obstructtive pulmonary disease, stable form, 114 male and 16 female, of whom 121 were smokers and 9 were non-smokers. Inclusive criteria were FEV1 < 50% from predicted (with moderate and severe level of the disease), the relation FEV1/FVC < 70%, the test of reversibility with β2-agonist < 15%. The patients were followed up for 18 months. They were evaluated at the start, and then at the end of the study. During the examination 9 patients were excluded because they did not obey recommendations of the examination, and three patients died during the examination. At the end of our study 77 patients in group I, 66 male and 11 female, were evaluated, and 41 patients, 35 male and 6 female, in group II. The patients were divided on the basis of BMI (body mass index), group I with BMI from 21 to 28 kg/m2 and group II with BMI < 21 kg/m2 . The mean age of the patients was 63 ± 7.2 years in group I, and 68 ± 8.3 in group II. The values of FEV1 at the start were 1.33 ± 0.35L (43 ± 8.1%) in group I, and 0.89 ± 0.27 L (28 ± 7.9%) in group II. Both were significantly lower in group II (p < 0.001). At the end of the study the values of FEV1 were lower in both groups than at the start (Fig. 1). At the start of the study SGRQ scores in group I were significantly lower (p < 0.001) than in group II. This indicated a better quality of life in patients with BMI from 21 to 28 kg/m2 . The SGRQ scores at the end of the study were also significantly lower in group I (p < 0.001). And they were lower than at the start in both groups, indicating a better quality of life in patients with COPD after18 months’ regular use of therapy (Fig. 2). The values of Pearson’s coefficient r = -0.49 (p < 0.05) in group I and r = -0.35 (0.05) in group II, shows that between these two variables there is an indirect, or negative correlation; lower values of FEV1 are associated with higher SGRQ total scores. It can be concluded that regular use of therapy for controlling the disease leads to improved quality of life in COPD patients, which is not associated with improvement in lung function. Patients with malnutrition (BMI < 21kg/m2 ) have lower values of FEV1, and they have higher SGRQ scores of quality of life. High levels of SGRQ scores are associated with lower values of FEV1. Key words: COPD, therapy, quality of life, forced expiratory volume in one second, body mass index.
Keywords: COPD; therapy; forced expiratory volume in one second; body mass index